1995
DOI: 10.1007/bf03160681
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vertebrate herbivory on plant community structure in the coastal marshes of the Pearl River, Louisiana, USA

Abstract: In this study, we investigated the impacts of herbivory by the introduced aquatic herbivore, nutria (Myocastor coypus), on three marsh communities of the Pearl River using fenced exclosures and control plots. Although total community above-ground biomass was reduced by 30% in the plots exposed to herbivory as compared to those protected from herbivory, we found species richness to be unaffected. When individual species were examined within each community, Panicurn virgatum and Aster subulatus were found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…In recent years, however, consumers have been identified as important controllers of salt marsh productivity, whether the consumer is mammalian (feral horses (Turner 1987, Furbish andAlbano 1994), rodents (Gough andGrace 1998, Crain 2008), hares (van der Wal et al 2000) or nutria (Evans 1970, Taylor andGrace 1995)), avian (snow geese Odum 1983, Jeffries 1997)), or invertebrate (crabs (Jackewicz 1973, Kraeuter and Wolf 1974, Pennings et al 1998, Bortolus and Irabarne 1999 or periwinkle snails Bertness 2002)). Insects also affect salt marsh biomass, at least in some cases (Bertness et al 1987, Bertness and Shumway 1993, Daehler and Strong 1995, Daehler and Strong 1996.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, however, consumers have been identified as important controllers of salt marsh productivity, whether the consumer is mammalian (feral horses (Turner 1987, Furbish andAlbano 1994), rodents (Gough andGrace 1998, Crain 2008), hares (van der Wal et al 2000) or nutria (Evans 1970, Taylor andGrace 1995)), avian (snow geese Odum 1983, Jeffries 1997)), or invertebrate (crabs (Jackewicz 1973, Kraeuter and Wolf 1974, Pennings et al 1998, Bortolus and Irabarne 1999 or periwinkle snails Bertness 2002)). Insects also affect salt marsh biomass, at least in some cases (Bertness et al 1987, Bertness and Shumway 1993, Daehler and Strong 1995, Daehler and Strong 1996.…”
Section: Discussionmentioning
confidence: 99%
“…Results from exclosure studies conducted in mesohaline marshes by Chabreck (1959) indicated that plots protected from herbivory possessed 40% greater standing crop than unprotected plots. In an earlier study of the Pearl River (Taylor and Grace 1995), biomass increased 30% in plots protected from herbivory in fresh, oligohaline, and mesohaline marshes. Since that earlier study, which took place in 1990-91, our observations indicate that populations of nutria and wild boar (Sus scrofa L.) have increased substantially.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most intense examples of herbivory reported are those dealing with muskrat (Ondotra zibethica rivalicius Bangs;O'Neil 1949), snow geese (Chen caerulescens L.; Adams 1956, Bazely andJefferies 1986), and nutria (Myocastor coypus Molina;Chabreck 1959, Fuller et al 1985, Shaffer et al 1992, Nyman et al 1993, Taylor and Grace 1995, Taylor et al 1995. Throughout the region, however, a range of different effects has been observed (Nyman et al 1993, Taylor and Grace 1995, Grace and Ford 1996. The effects of herbivores on coastal wetlands have also been shown to depend on a number of factors such as food preference (Shaffer et al 1992), animal density (Linscombe et al 1981), and habitat conditions (Shaffer et al 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure the effect of herbivory, investigators usually compare the growth, survival, or reproduction (henceforth called performance) of target plants in experimental treatments with herbivores excluded versus herbivores not excluded. Results of herbivore-exclusion experiments conducted in wetlands suggest that herbivory may reduce plant performance signficantly (Smith 1983, Jensen 1985, Bazely and Jefferies 1986, Belanger and Bedard 1994, Taylor and Grace 1995, Mulder 1998. To measure the effect of competition, investigators usually compare the performance of target plants in experimental treatments with neighboring plants removed versus neighbors left intact.…”
Section: Introductionmentioning
confidence: 99%